Regulation of anti-tumour effects of Paris polyphylla saponins via ROS: molecular mechanisms and therapeutic potentials - Liu, Jia; Mu, Yongping; Qi, Ke; Li, Jiayi; Hu, Yang (Frontiers in Pharmacology, 2025)
Reactive oxygen species (ROS) exhibit a dual regulatory role in cancer biology. While moderate ROS levels promote tumorigenesis via DNA mutagenesis, excessive ROS accumulation induces cancer cell death through oxidative stress. Therefore, ROS homeostasis represents a promising therapeutic target in oncology. Collectively, ROS exhibit context-dependent and multifaceted roles in cancer progression. Emerging evidence highlights the anticancer potential of traditional Chinese medicine (TCM), particularly Paris polyphylla saponin (PPS). PPS modulates oxidative stress through precision targeting of ROS-associated signaling pathways, thereby inducing apoptosis, cell cycle arrest, autophagy, and ferroptosis. These mechanisms collectively suppress tumor growth, metastasis, and angiogenesis, while concurrently mitigating inflammatory responses. Notably, PPS potentiates the efficacy of chemotherapeutic agents by reversing multidrug resistance in refractory cancer cells. The bioactive constituents of PPS, polyphyllin and polyphyllinositol, exhibit potent antitumor activity in preclinical models. This study systematically elucidates the molecular mechanisms underlying PPS-mediated anticancer effects via ROS targeting, offering a robust theoretical framework and translational insights for future oncology research.